Perception, Training and Adoption of Cloud Computing by Library Staff in Selected University Libraries in Kwara State, Nigeria - Bolaji, Muzbaudeen Kayode; Aboki, Nathaniel; Yusuf, Abdullahi Adebola; Gold, Mariam Ajoke (Communicate: Journal of Library and Information Science, 2025)
The study examined the perception, training and adoption of cloud computing by library staff in selected university libraries in Kwara State, Nigeria. A descriptive survey research design was employed, and a purposive sampling techniques was used to select one public, state and private-owned universities in Kwara State, for a total population of 178 library staff. The estimated sample size was determined to be 108 library staff; data were collected from 105 respondents using structured questionnaires. The analysis was conducted using frequency counts, mean, and standard deviation. Findings revealed that majority of the respondents had a positive perception of cloud computing adoption. Specifically, 87.6% of respondents agreed that cloud computing reduces operational costs, while 85.7% affirmed its role in enhancing access to information resources. Furthermore, 81% agreed that cloud computing improves service delivery and data security. The study also established that training is a significant determinant of cloud computing adoption. About 87.6% of the respondents indicated that training improved their knowledge and confidence in using cloud-based services. However, the study identified major challenges, including poor internet connectivity, inadequate technical support, data security concerns, and lack of funding, all cited by 85.7% of respondents confirming that staff attitudes influence successful implementation. The study concludes that positive perception and adequate training are crucial for effective adoption of cloud computing in university libraries. It recommends regular training programmes, investment in ICT infrastructure, and increased funding support to overcome the identified challenges and facilitate efficient cloud computing integration in academic libraries.